Preparation and nutritional evaluation of wastelage using poultry droppings and napier grass (Bangladesh Journal of Animal Science, 2019)
An experiment was conducted with Napier grass (NG) treated with Poultry droppings (PD) and rice straw and ensiled with molasses to increase the nutritional and preservation quality of Napier grass. Chopped Napier grass was preserved in plastic containers under airtight condition at room temperature based on the treatments T0 (0% PD), T1 (15% PD), T2 (30% PD) and T3 (45% PD) with 5% molasses and 20% rice straw as fresh basis in each treatment to investigate physical quality, chemical composition, in vitro organic matter digestibility (IVOMD) and metabolizable energy (ME) content at 0, 30, 45, 60 and 75 days. The physical quality (color, smell, and hardness) of Napier grass mixer were improved in Poultry droppings added treatments till 75 days of ensiling. The pH value was decreased (P